Late Quaternary formation of the Miaoli Tableland in northwest Taiwan, an interplay of tectonic uplift and fluvial processes dated by OSL. (March 2023) - Liu, Shih-Hung; Lüthgens, Christopher; Hardt, Jacob; Hebenstreit, Robert; Böse, Margot; Frechen, Manfred
Abstract: The "tablelands" in Taiwan are sedimentary terraces occurring in the foreland basin west of the Neogene mountain ranges. The Miaoli Tableland consists of elevated Late Quaternary sedimentary successions, representing a change from tidal to coastal and fluvial to eolian depositional environments. The present-day morphology is a result of combined processes, including differential tectonic uplift, ongoing fluvial aggradation, and incision. Selected deposits in 10 outcrops were sampled and studied by optical dating. The deposition of fluvial sediments started after the last interglacial (<100 ka) in the southeast of the tablelands. Uplift and sea-level lowering caused a base-level fall, resulting in a stepwise redeposition of the fluvial sediments. Additionally, enhanced remobilization of fluvial sediments occurred during the cold/dry climate during Marine Oxygen Isotope Stages (MIS) 4 and 2. The depositional ages of the coastal sediments enabled the estimation of long-term uplift rates of ca. 0.5 to 3.5 mm/yr. The eolian cover sediments yielded MIS 3 (east) to Holocene ages (west). Our results provide new insight into the interplay of climate, sea-level changes, remobilization of sediments, and tectonism leading to tableland formation during the Late Quaternary.